Edukasi Teknik Menyusui yang Benar pada Bayi dalam Meningkatkan Pengetahuan Ibu Postpartum Di Rumah Sakit Tentara TK 01.07.01 Pematangsiantar [Education On Proper Breastfeeding Techniques for Infants to Improve Postpartum Mothers' Knowledge at TK 01.07.01 Military Hospital Pematangsiantar] - Purba, Nova Necis Natalia; Damanik, Derma Wani (UKInstitute, 2025)
Abstract. The postpartum period is the period following the delivery of the placenta until the reproductive organs return to their normal state, lasting 6 weeks or 42 days. One of the problems frequently faced by breastfeeding mothers is a lack of knowledge about proper breastfeeding techniques. Education about breastfeeding techniques is an important step in addressing this issue. The goal of breastfeeding technique education is to improve the baby's attachment to the breast and the mother's ability to position the baby correctly. The initial assessment revealed that postpartum mothers did not yet understand proper breastfeeding techniques, including proper positioning and attachment. After being educated on proper breastfeeding techniques, their knowledge increased, and they were able to explain and practice breastfeeding techniques as taught. Education about proper breastfeeding techniques has been proven effective in improving postpartum mothers' knowledge, reducing complaints, and increasing confidence and comfort in breastfeeding. Abstrak. Masa postpartum merupakan masa setelah lahirnya plasenta hingga organ reproduksi kembali seperti semula, berlangsung selama 6 minggu atau 42 hari. Salah satu masalah yang sering dihadapi ibu menyusui adalah kurangnya pengetahuan tentang teknik menyusui yang benar. Edukasi mengenai teknik menyusui merupakan Langkah penting dalam mengatasi masalah tersebut. Tujuan dari edukasi teknik menyusui yaitu untuk meningkatkan perlekatan bayi pada payudara ibu, kemampuan ibu untuk meningkatkan posisi bayi dengan benar. Hasil pada pengkajian awal, ibu postpartum belum memahami tentang teknik menyusui yang benar, termasuk posisi dan perlekatan yang tepat, setelah diberikan edukasi teknik menyusui yang benar, pengetahuan ibu meningkat, ibu mampu menjelaskan dan mempraktikan teknik menyusui sesuai dengan yang diajarkan. Edukasi teknik menyusui yang benar terbukti efektif dalam meningkatkan pengetahuan ibu postpartum, dapat mengurangi keluhan serta meningkatkan percaya diri dan kenyamanan dalam menyusui.